PENGGUNAAN MEDIA PEMBELAJARAN SEDOTAN (DRINGKING STRAWS) DAN KANTONG DALAM MENINGKATKAN HASIL BELAJAR - An Nisa, Winni (Almeera Education, 2023)
In learning mathematics, teachers only use book media and lecture methods, namely the teacher explains then students take notes. Especially in the numerical material, the teacher has not used the maximum learning media, therefore making students unable to understand the numerical material as a whole. As for this research, formulating the problem